Prevalence and risk factors of healthcare-associated infections in Thailand 2018: A point-prevalence survey - V. Moolasart (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND | 2019. Background: Healthcare-associated infections (HAIs) are one of the most important challenges in contemporary medicine. Surveillance of HAIs is essential for infection control programs and reduction of HAIs. Materials and Methods: A national point prevalence survey was conducted in accordance with the protocol of the HAIs Control Group of Thailand between 19 and 23 February, 2018 in 37 randomly selected hospitals across Thailand. Thailand's protocol followed the United States of America's Centers for Disease Control and Prevention surveillance definition of HAIs. Results: There were 12,643 patients admitted to the participating hospitals. The point prevalence of HAIs was 4.2% (528/12,643, 95% CI 3.82 to 4.54). The highest prevalence of HAIs was observed in patients younger than one year (4.6%, 95% CI 3.36 to 5.88) and older than 60 years (5.9%, 95% CI 5.24 to 6.60) at government university hospitals (5.4%, 95% CI 4.37 to 6.35) and in intensive care units (ICU) wards (14.6%, 95% CI 11.60 to 17.60). The most common procedures associated with HAIs were tracheostomy (27.3%, 95% CI 22.86 to 31.78), central line (17.6%, 95% CI 13.70 to 21.44), endotracheal tube (13.8%, 95% CI 11.83 to 15.85), and urinary catheter (9.6%, 95% CI 8.55 to 10.73). Multivariate analysis showed HAIs were significantly associated with patient younger than one year, government university hospital, government tertiary hospital, government secondary hospital, treatment in ICU, having urinary catheterization, central line, having a tracheostomy, on respirator, and surgery management (all p<0.05). The most common HAIs were ventilator-associated pneumonia (26.9%), followed by nonventilator- associated pneumonia (19.0%), catheter-associated urinary tract infection (13.5%), and surgery site infection (11.2%). The most common causative bacteria were gram-negative bacteria, of which Klebsiella pneumoniae (18.5%) was the most common, followed by Acinetobacter baumannii (17.8%) and Pseudomonas aeruginosa (12.6%). Conclusion: The point prevalence of HAIs was 4.2% with a decreasing trend. Pneumonia and gram-negative bacteria were prominent problems among inpatients. Continued efforts to prevent and control HAIs are effective and should be further strengthened.